Biogas improvement as renewable energy through conversion into methanol: A perspective of new catalysts based on nanomaterials and metal organic frameworks - Sánchez, Antoni (Frontiers in Nanotechnology, 2022)
In recent years, the high cost and availability of energy sources have boosted the implementation of different typologies of renewable energy. Among them, methane contained in biogas from anaerobic digestion has gained special relevance, since it also permits the management of a big amount of organic waste, which is locally available, and the capture and storage of carbon. However, methane from biogas presents some problems as energy source: i) it is a gas, so its storage is costly and complicated, ii) it is not pure, being carbon dioxide the main by-product of anaerobic digestion (30-50%), iii) it is explosive with oxygen under some conditions and iv) it has a high global warming potential (25 time of that of carbon dioxide). Consequently, the conversion of biogas to methanol appears as an attractive way to overcome these problems. These means the conversion to both methane and carbon dioxide into methanol in one oxidation and one reduction reaction, respectively. In this complex system, the use of effective and selective catalysts for both reactions is a critical issue. Regarding this, nanomaterials embedded in metal organic frameworks have been recently tested for both reactions, with very satisfactory results when compared to traditional materials such as zeolites. In this review paper, the recent catalyst configurations of nanoparticles as active catalyst and metal organic frameworks as support material are reviewed and discussed. The main challenges for the future development of this technology are also highlighted, being the cost in environmental and economic terms and the process scale-up the main restrictions for a full-scale implementation.